Cannabinoid receptor 2 expression in early-stage non-small cell lung cancers identifies patients with good prognosis and longer survival - Vidlarova, Monika; Berta, Emil; Prasil, Petr; Prokopova, Andrea; Gurska, Sona; Khoylou, Marta; Rehulkova, Alona; Kourilova, Pavla; Chudacek, Josef; Szkorupa, Marek; Klein, Jiri; Skarda, Jozef; et al. (Translational lung cancer research, 2022)
BACKGROUND: Non-small cell lung cancer (NSCLC) is a leading cause of cancer-related death with a 5-year survival of only 21%. Reliable prognostic and/or predictive biomarkers are needed to improve NSCLC patient stratification, particularly in curative disease stages. Since the endogenous cannabinoid system is involved in both carcinogenesis and anticancer immune defense, we hypothesized that tumor tissue expression of cannabinoid 1 and 2 receptors (CB1 and CB2) may affect survival. METHODS: Tumor tissue samples collected from 100 NSCLC patients undergoing radical surgery were analyzed for CB1 and CB2 gene and protein expression using the quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC). The gene and protein expression data were correlated with disease stage, histology, tumor grading, application of chemotherapy, and survival. Additional paired tumor and normal tissue samples of 10 NSCLC patients were analyzed independently for comparative analysis of CB1 and CB2 gene expression. RESULTS: Patients with tumors expressing the CB2 gene had significantly longer overall survival (OS) (P<0.001), cancer specific survival (CSS) (P=0.002), and disease-free survival (DFS) (P<0.001). They also presented with fewer lymph node metastases at the time of surgery (P=0.011). A multivariate analysis identified CB2 tumor tissue gene expression as a positive prognostic factor for CSS [hazard ratio (HR) =0.274; P=0.013] and DFS (HR =0.322; P=0.009), and increased CSS. High CB2 gene and protein expression were detected in 79.6% and 31.5% of the tested tumor tissue samples, respectively. Neither CB1 gene nor CB1 or CB2 protein expression affected survival. When comparing paired tumor and tumor-free lung tissue samples, we observed reduced CB1 (P=0.008) and CB1 (P=0.056) gene expression in tumor tissues. CONCLUSIONS: In NSCLC patients undergoing radical surgery, expression of the CB1 and CB2 receptor genes is significantly decreased in neoplastic versus tumor-free lung tissue. CB2 tumor tissue gene expression is strongly associated with longer survival (OS, CSS, DFS) and fewer lymph node metastases at the time of surgery. More studies are needed to evaluate its role as a biomarker in NSCLC and to investigate the potential use of CB2 modulators to treat or prevent lung cancers.
Keywords: cannabinoid receptor; patient survival; cannabinoids; metastasis; Lung cancer